Diarrhea in solid-organ transplant recipients: a review of the evidence. (October 2013) - Pant, Chaitanya; Deshpande, Abhishek; Larson, Anne; O'Connor, Judith; Rolston, David D.K.; Sferra, Thomas J.
Abstract Objective: To provide a comprehensive review of the literature as it relates to diarrhea in solid organ transplant (SOT) recipients. In this article, we review the epidemiology, pathogenesis, clinical manifestations, diagnosis and management of diarrhea in SOT recipients and discuss recent advances and challenges. Methods: Two investigators conducted independent literature searches using PubMed, Web of Science, and Scopus until January 1st, 2013. All databases were searched using a combination of the terms diarrhea, solid organ transplant, SOT, transplant associated diarrhea, and transplant recipients. Articles that discussed diarrhea in SOT recipients were reviewed and relevant cross-references also read and evaluated for inclusion. Selection bias could be a possible limitation of the approach used in selecting or finding articles for this article. Findings: Post-transplant diarrhea is a common and distressing occurrence in patients, which can have significant deleterious effects on the clinical course and well-being of the organ recipient. A majority of cases are due to infectious and drug-related etiologies. However, various other etiologies including inflammatory bowel disease must be considered in the differential diagnosis. A step-wise, informed approach to post-transplant diarrhea will help the clinician achieve the best diagnostic yield. The use of diagnostic endoscopy should be preceded by exclusion of an infectious or drug-related cause of diarrhea. Empiric management with antidiarrheal agents, probiotics, and lactose-free diets may have a role in managing patients for whom no cause can be determined even after an extensive investigation. Conclusions: Physicians should be familiar with the common etiologies that result in post-transplant diarrhea. A directed approach to diagnosis and treatment will not only help to resolve the diarrhea but also prevent potentially life-threatening consequences including loss of the graft as well. Prospective studies are required to determine the etiology of post-transplant diarrhea in different clinical and geographic settings.